2013
DOI: 10.5194/bg-10-4287-2013
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of <sup>134</sup>Cs and <sup>137</sup>Cs in surface seawater in the western and central North Pacific after the Fukushima Dai-ichi nuclear power plant accident

Abstract: Abstract. The horizontal distribution of radioactive cesium (Cs) derived from the Fukushima Dai-ichi nuclear power plant (FNPP) in the North Pacific is still unclear due to the limitation of direct measurement of the seawater in the open ocean. We present the result of direct observation of radioactive Cs in surface seawater collected from a broad area in the western and central North Pacific in July 2011, October 2011 and July 2012. We also conducted a simple particle tracking experiment to estimate the quali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
85
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 26 publications
11
85
0
Order By: Relevance
“…These were possibly due to advection of the contaminated waters from the coastal area of the FNPP1. Aoyama et al (2013) and Kaeriyama et al (2013) also reported eastward movement of direct discharged radiocesium from FNPP1 in the transition region.…”
Section: Discussionmentioning
confidence: 83%
“…These were possibly due to advection of the contaminated waters from the coastal area of the FNPP1. Aoyama et al (2013) and Kaeriyama et al (2013) also reported eastward movement of direct discharged radiocesium from FNPP1 in the transition region.…”
Section: Discussionmentioning
confidence: 83%
“…The large anticyclonic Tohoku eddy (TE,) with the center at around 39 • N, 144 • E in March 2011, was sampled after the accident in the two R/V cruises in June (Buesseler et al, 2012) and July 2011 (Kaeriyama et al, 2013), showing large concentrations of 137 Cs and 134 Cs. The anticyclonic Hokkaido eddy (HE), genetically connected with the TE, originated in the middle of May 2011 with the center at around 40 • N, 145 • E. After that it captured some contaminated water from the TE.…”
Section: Resultsmentioning
confidence: 99%
“…2a by the dashed line), after the day of the accident on 11 March 2011. The TE was sampled on 10 and 11 June 2011 by Buesseler et al (2012) along the transect 35.5-38 • N, 144 • E shown in (c) and at the end of July 2011 by Kaeriyama et al (2013) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations